SubCAS: A Portable, Submersible Hyperbaric Chamber to Collect Living Mesophotic Fishes - Shepherd, Bart; Wandell, Matt; Pinheiro, Hudson T.; Rocha, Luiz A. (Frontiers in Marine Science, 2018)
Accompanying the recent technological innovations in remotely operated vehicles, submersibles, technical SCUBA, and closed-circuit rebreather diving gear, new discoveries are being made on mesophotic coral ecosystems around the world. However, collecting live fishes from mesophotic depths (60-150m) is challenging, given the difficulty of accessing the habitat, catching the fishes, and the barotrauma that can result from rapid decompression during their transport to the surface. Here, we designed and tested the performance of a portable, submersible hyperbaric chamber, the SubCAS, which we used to safely surface reef fishes from mesophotic depths. During six expeditions between 2014 and 2017 to the Philippines, Vanuatu, Palau and Pohnpei, we assessed the survival of 174 fishes caught between 60 and 150 m depth and decompressed using this chamber. A total of 155 (89.1%) fishes survived decompression, and 143 of 148 specimens shipped (96.6%) survived air cargo transport from remote field sites to the Steinhart Aquarium at the California Academy of Sciences. Survival was significantly related to taxonomic family, with Pomacentridae and Apogonidae showing the highest mortality. Collection depth, fish body size, and length of decompression had no relation to survivorship. Significant interactions between individual decompression events and both fish body size and taxonomic family indicate that low survival was associated with specific SubCAS trials. The SubCAS has allowed us to reliably surface charismatic fishes previously unknown to science and maintain them in aquaria for research and public engagement purposes. This opportunity facilitates a direct connection between our more than one million annual visitors and the wonders of exploration and the science of mesophotic coral ecosystems.